PENERAPAN MODEL PEMBELAJARAN E-LEARING DI ERA DIGITALISASI GUNA MENINGKATKAN MINAT BELAJAR SISWA - Khopipah, Siti Khopipah (Journal of Business Education and Social, 2022)
The use of technology in the learning process has an important role in improving the quality of education, so that learning is held to be more effective and efficient. Therefore, the existence of technology is expected to create a learning atmosphere that stimulates students to explore and explore their potential to the fullest. The existence of 21st century learning that involves information and communication technology in educational activities, makes e-learning one of the important things in supporting the implementation of learning that involves digital technology to increase student interest in learning. This study aims to increase students' interest in learning through the E-Learning learning model in the digitalization era. The research method used is a qualitative research method with a descriptive approach which is carried out with interviews to explore information which is carried out for 3 days. The subjects in this study were at the SMK level. The results of the study explain that the use of e-learning in learning activities is quite effective in increasing student interest in learning, but because its use is less familiar, there are still some students who are less interested in e-learning-based learning. Keywords: E-learning, Interest in Learning